Modeling the Hemodynamic Characteristics of the Carrotic Care Blood Based on Computer Tomography - D. A. Baliuk; N. S. Davydova; M. M. Mezhennaya; M. V. Davydov (Цифровая трансформация, 2021)
The purpose of the work was to conduct modeling of hemodynamics of blood flow and study the hemodynamic characteristics of blood vessels. 3D models of the carotid artery were constructed based on images of a computer tomography in the 3D SLICER software package. The resulting model phantoms are modeled in the FlowVision software package using the finite element method. The most dangerous pathologies of the geometry of the vascular bed affecting the change in the hemodynamic characteristics of the blood flow were identified. The greatest danger in lowering the flow velocity in the lumen of the vessel was the tortuosity pathology (up to 30%). Pathology during the formation of aneurysms to a small extent influenced the decrease in speed (up to 8%). The danger of this pathology was to increase the pressure exerted by the blood stream on the wall of the aneurysm. The formation of atherosclerotic plaques in the lumen of the vessel led to a slowdown (up to 25%) and an increase in pressure in the area of plaque formation.